Research on the oil retention effect of pneumatic oil barriers under current and wave action - Hao Liu; Hongyuan Sun; Bo Jiao; Haihua Lin; Guoxing Wang (PLoS ONE, 2025)
The pneumatic oil barrier is a novel device that intercepts oil spills by releasing high-pressure gas underwater to form a curtain of bubbles. However, its performance can be affected by both internal factors and external influences like water flow and waves, leading to varying degrees of oil interception failure and reduced effectiveness. This study combines physical experiments with numerical simulations to analyze the impact of nozzle parameters, arrangement, flow velocity, and wave effects on oil interception loss and effective containment distance under uniform flow and wave conditions. The findings establish relationships between these factors and interception efficiency, revealing reasons for changes in effective containment distance through flow field analysis. The research indicates that the pneumatic oil barrier is effective for floating oil with flow velocities below 0.15 m/s; the optimal nozzle diameter is 1.5 mm, as increasing it affects the stability of horizontal flow and oil layers. Additionally, a dual-pipe arrangement produces a wider and more stable horizontal flow on the water surface, enhancing oil interception effectiveness, while waves can destabilize oil layers, reducing effective containment distance.